Mechanisms of Esophageal Protection, Gastroprotection and Ulcer Healing by Melatonin. Implications for the Therapeutic use of Melatonin in Gastroesophageal Reflux Disease (GERD) and Peptic Ulcer Disease - Brzozowska, Iwona; Strzalka, Malgorzata; Drozdowicz, Danuta; J. Konturek, Stanislaw; Brzozowski, Tomasz (Current Pharmaceutical Design, 2014)
Melatonin is a potent reactive oxygen metabolite scavenger and antioxidant that has been shown to influence many physiological functions of the gastrointestinal (GI) tract including secretion, motility, digestion and absorption of nutrients. The role of melatonin in gastroduodenal defense and ulcer healing has been the subject of recent investigations. Melatonin produced in the GI mucosa plays an important role in protection against noxious agents thus contributing to the maintenance of GI integrity and to esophageal protection, gastroprotection and ulcer healing. This review was designed to summarize the involvement of melatonin, conventionally considered as a major hormone of the pineal gland, in the maintenance of gastric mucosal integrity, gastroprotection, ulcer healing and intestinal disorders. Melatonin was originally shown to attenuate gastric mucosal lesions but controversy exists in the literature as to whether melatonin derived from the pineal gland, considered as the major source of this indole, or rather gastrointestinal melatonin plays predominant role in gastroprotection. Intragastric and central administration of exogenous melatonin and L-tryptophan, this indoleamine precursor, affords protection against gastric hemorrhagic damage caused by the exposure of gastric mucosa to variety of non-topical and topical ulcerogens such as stress, ethanol and ischemia-reperfusion. The speed of ulcer healing in experimental animals and humans is accelerated by melatonin. This indoleamine could be also effective against the esophageal lesions provoked by reflux esophagitis in animal models and prevents the incidence of GERD in humans. The melatonin-induced gastroprotection is accompanied by an increase in gastric blood flow, plasma melatonin concentration, enhancement in mucosal generation of PGE2, luminal NO content and plasma gastrin levels. Melatonin scavenges reactive oxygen metabolites, exerts anti-oxidizing and anti-inflammatory actions and inhibits the formation of metalloproteinases- 3 and -9; both implicated in the pathogenesis of gastrointestinal injury and formation of gastric ulcers. Blockade of MT2 receptors by luzindole, significantly attenuated melatonin- and L-tryptophan-induced protection and increased the speed of ulcer healing and these effects were accompanied by an increase in the GBF and luminal content of NO suggesting that melatonin exhibits gastroprotection and hyperemia via activation of MT2 receptors and release of NO. The accumulated evidence indicates that the melatonin-induced gastroprotection and the enhancement in healing rate of gastric ulcers may involve the gastroprotective factors derived from the activation of PG/COX and NO/NOS systems as well as gastrin which also was shown to exhibit protective and trophic effects in the upper GItract. Interestingly, pinealectomy, which suppressed plasma melatonin levels, markedly exacerbated gastric lesions induced by topical and non-topical ulcerogens and these effects are counteracted by a concurrent supplementation with melatonin. Evidence is provided that exogenous melatonin and that converted from its precursor, L-tryptophan, attenuates acute gastric lesions and accelerates ulcer healing via interaction with MT2 receptors due to an enhancement of gastric microcirculation, probably mediated by NO and PG derived from NOS and COX-1 and COX-2 overexpression and activity. The pineal gland plays an important role in the limitation of gastric mucosal injury and the acceleration of ulcer healing via releasing endogenous melatonin, which attenuates oxidative stress and exerts antiinflammatory action.
Keywords: active oxygen metabolites